Breech presentation: Clinical practice guidelines from the French College of Gynaecologists and Obstetricians (CNGOF). (September 2020) - Sentilhes, Loïc; Schmitz, Thomas; Azria, Elie; Gallot, Denis; Ducarme, Guillaume; Korb, Diane; Mattuizzi, Aurélien; Parant, Olivier; Sananès, Nicolas; Baumann, Sophie; Rozenberg, Patrick; Sénat, Marie-Victoire; et al.
Abstract: Objective: To determine the optimal management of singleton fetuses in breech presentation. Materials and methods: Consultation of the PubMed database, the Cochrane Library and guidelines issued by the French and foreign obstetrical societies or colleges. Results: In France, 5% of women have breech deliveries (level of evidence [LE] 3). One third of them have a planned vaginal delivery (LE3), and 70% of these give birth vaginally (LE3). External cephalic version (ECV) is associated with lower rates of both breech presentation at birth (LE2) and of cesarean deliveries (LE3) without any increase in severe maternal (LE3) or perinatal morbidity (LE3). Women with a fetus in breech presentation at term should be informed that ECV can be attempted starting at 36 weeks of gestation (professional consensus). Planned vaginal delivery of breech presentation may be associated with a higher risk of composite perinatal mortality or serious neonatal morbidity than planned cesarean birth (LE2). These two modes do not differ for neurodevelopmental outcomes at two years (LE2), cognitive and psychomotor outcomes between 5 and 8 years (LE3), or adult intellectual performance (LE4). Short- and long-term maternal complications appear similar in the two groups, unless subsequent pregnancies are under consideration. Pregnancies after a cesarean delivery are at higher risk of uterine rupture, placenta accreta spectrum disorders, and hysterectomy (LE2). Women who want a planned vaginal delivery should be offered a pelvimetry at term (Grade C) and should have ultrasonography to verify that the fetal head is not hyperextended (professional consensus) to plan their mode of delivery. Complete breech presentation, a previous cesarean, nulliparity, and term prelabor rupture of membranes are not, each one by itself, per se contraindications to planned vaginal delivery (professional consensus). Term breech presentation is not a contraindication to labor induction when the criteria for planned vaginal delivery are met (Grade C). Conclusion: In cases of breech presentation at term, the child and the mother are at low risk of severe morbidity after either planned vaginal or planned cesarean delivery. The French College of Obstetricians and Gynecologists (CNGOF) considers that planned vaginal delivery is a reasonable option in most cases (professional consensus). The decision about the planned route of delivery should be shared by the woman and her healthcare provider, who must respect her right to autonomy.